2022
DOI: 10.3390/buildings12071024
|View full text |Cite
|
Sign up to set email alerts
|

Development of Self-Compacting Concrete Incorporating Rice Husk Ash with Waste Galvanized Copper Wire Fiber

Abstract: This research work is devoted to the experimental investigation of both rheological and mechanical properties of self-compacting concrete (SCC) produced with waste galvanized copper wire fiber and rice husk ash (RHA). In the study, three different volume fractions of 0.5 p to 0.75 percent, 1 percent of scrap copper wire fiber as reinforcing material, and 2 percent RHA as cement replacement were used. To evaluate the fresh characteristics of SCC, the slump flow, J-ring, and V-funnel experiments were conducted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 32 publications
(48 reference statements)
1
3
0
Order By: Relevance
“…Therefore, the compressive strength also decreases slightly. The results are aligned with the previous researcher's findings [42]. This condition is confirmed by a decrease in the compressive strength test results for SCC in the variant with the addition of PET fiber and fly ash powder.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, the compressive strength also decreases slightly. The results are aligned with the previous researcher's findings [42]. This condition is confirmed by a decrease in the compressive strength test results for SCC in the variant with the addition of PET fiber and fly ash powder.…”
Section: Discussionsupporting
confidence: 90%
“…This study also conducted non-destructive testing (NDT) with an ultrasonic pulse velocity (UPV) test as an alternative method, considering that the UPV test for concrete quality assessment has been in practice for decades. Previous studies have reported a good correlation between the SCC compressive strength and UPV test results [42,43]. However, specific studies on the application of NDT to concrete with plastic fibers having different densities and thermal conductivities compared to hardened concrete as a matrix still need to be made available, especially for the particular case of plastic fiber-reinforced SCC.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, research was often limited to the workability of fiber-reinforced concrete, such as the influence of fiber distribution on concrete fluidity and the influence of fiber length on concrete cohesion. Furthermore, mechanical properties are important in terms of whether materials or structures can meet the usage requirements, and thus, many experts have started to study the impact of various fibers on the basic mechanical properties of concrete [ 10 , 11 , 12 ]. M. G. Alberti and K. M. A. Hossain et al studied the effects of different fiber volume ratios on the basic mechanical properties of polyacrylonitrile fiber self-compacting concrete and polyvinyl alcohol fiber self-compacting concrete and concluded that with increasing fiber content, the splitting tensile strength of self-compacting concrete gradually increases and the compressive strength gradually decreases [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their study showed that the rice husk-bark ash is effective for producing SCC with 30% of rice husk-bark ash replacement level. On the other work, experimentally investigatethe rheological and mechanical properties of SCC produced with rice husk ash (RHA) [40] . The suitability of untreated rice husk ash as a supplementary to the OPC and fine aggregates (FA) in high strength SCC was also investigated in terms of mechanical properties as well as environmental impact assessments (EIA) [41] .…”
Section: Introductionmentioning
confidence: 99%